2020
DOI: 10.1111/irv.12748
|View full text |Cite
|
Sign up to set email alerts
|

Applying the moving epidemic method to determine influenza epidemic and intensity thresholds using influenza‐like illness surveillance data 2009‐2018 in Tunisia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, ILI cases were not tested in a laboratory and may have been due to COVID-19 as it was the circulating virus during that time. The epidemics lasted about 7-8 weeks, less than the average duration estimated from other studies [ 5 , 9 , 11 , 12 , 19 , 20 ], which could be due to limited data seasons and variable data points. The epidemic threshold obtained from the MEM model was slightly higher than the currently used cumulative sum 2 method, which facilitates using the value of the cumulative sum method as an alert to initiate public health measures to control ILI spread no matter what the causative agent is.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, ILI cases were not tested in a laboratory and may have been due to COVID-19 as it was the circulating virus during that time. The epidemics lasted about 7-8 weeks, less than the average duration estimated from other studies [ 5 , 9 , 11 , 12 , 19 , 20 ], which could be due to limited data seasons and variable data points. The epidemic threshold obtained from the MEM model was slightly higher than the currently used cumulative sum 2 method, which facilitates using the value of the cumulative sum method as an alert to initiate public health measures to control ILI spread no matter what the causative agent is.…”
Section: Discussionmentioning
confidence: 68%
“…The most recent approach to estimating influenza thresholds and characterizing influenza epidemics is using the moving epidemic method (MEM). A method has recently been used in several countries, including Arab nations [9] , [10] , [11] , as the standard for estimating influenza thresholds and intensity levels [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…8 Through both published and unpublished time-series analyses, countries in the region have demonstrated a more thorough understanding of influenza circulation patterns and seasonal trends, and some countries have determined epidemic thresholds to better guide their seasonal response to influenza spread. [9][10][11][12] In 2019, representatives from 14 ministries of health in the region received training in and began a systematic evaluation of their influenza surveillance systems based on CDC's guidelines for evaluating public health surveillance systems and used the findings for influenza surveillance program decision-making. 13,14 The substantial improvements in surveillance capacities supported by CDC ID in collaboration with WHO EMRO demonstrate commitment by national governments in EMR to prioritize programs for influenza surveillance, response, and preparedness and contribute data and specimens for consideration in global influenza vaccine composition recommendations.…”
Section: Evidence Of Expanded Regional Capacitiesmentioning
confidence: 99%
“…The moving epidemic method (MEM) was first put forward in Spain [11] and has been adopted as a routine surveillance program to establish the epidemic threshold and intensity levels in some temperate countries [12,13]. Increasing studies in other climate zones have also demonstrated the high goodness of fit of the threshold established by the MEM [14][15][16][17]. In China, there is no standard method for setting epidemic thresholds, so introducing a practical method for early influenza detection will be helpful to reduce the disease burden for Chinese people.…”
Section: Introductionmentioning
confidence: 99%